2022 Bern consensus statement on shoulder injury prevention, rehabilitation, and return to sport for athletes at all participation levels - Schwank, A.; Blazey, P.; Asker, M.; Møller, M.; Hägglund, M.; Gard, S.; Skazalski, C.; Haugsbø Andersson, S.; Horsley, I.; Whiteley, R.; Cools, A. M.; Bizzini, M.; et al. (Journal of Orthopaedic & Sports Physical Therapy, 2022)
There is an absence of high-quality evidence to support rehabilitation and return-to-sport decisions following shoulder injuries in athletes. The Athlete Shoulder Consensus Group was convened to lead a consensus process that aimed to produce best-practice guidance for clinicians, athletes, and coaches for managing shoulder injuries in sport. We developed the consensus via a 2-round Delphi process (involving more than 40 content and methods experts) and an in-person meeting. This consensus statement provides guidance with respect to load and risk management, supporting athlete shoulder rehabilitation, and decision making during the return-to-sport process. This statement is designed to offer clinicians the flexibility to apply principle-based approaches to managing the return-to-sport process within a variety of sporting backgrounds. The principles and consensus of experts working across multiple sports may provide a template for developing additional sport-specific guidance in the future.